2014
DOI: 10.1074/jbc.m114.559914
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations of Energy Metabolism Associated with Increased Levels of Mitochondrial Cholesterol in Niemann-Pick Type C1-deficient Cells

Abstract: Background: Endosomal cholesterol storage in Niemann-Pick type C1 deficiency is associated with elevated mitochondrial cholesterol and alterations in energy metabolism. Results: Blocking endosomal cholesterol transport to mitochondria prevented the metabolic alterations in NPC1-deficient cells. Conclusion: Mitochondrial cholesterol accumulation increases oxidative stress and alters energy metabolism. Significance: Mitochondrial cholesterol is a regulator of energy metabolism and mitochondrial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 56 publications
5
68
0
Order By: Relevance
“…This conclusion is further supported by our findings of downregulated expression of genes involved in the regulation of mitochondrial activity, including PGC1, cytochrome c, COX IV, and COX 8b, as well as the decreased expression of anti-oxidant genes such as GPX1, PRDX1, GSTA4, and SOD1 in NPC2-kd adipocytes. In accordance with the results from a recent study (18), our data clearly support the studies are needed to investigate the precise molecular mechanism for the role of NPC2 in the regulation of TLR signaling pathway activation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This conclusion is further supported by our findings of downregulated expression of genes involved in the regulation of mitochondrial activity, including PGC1, cytochrome c, COX IV, and COX 8b, as well as the decreased expression of anti-oxidant genes such as GPX1, PRDX1, GSTA4, and SOD1 in NPC2-kd adipocytes. In accordance with the results from a recent study (18), our data clearly support the studies are needed to investigate the precise molecular mechanism for the role of NPC2 in the regulation of TLR signaling pathway activation.…”
Section: Discussionsupporting
confidence: 81%
“…In another study, increased accumulation of mitochondrial cholesterol and mitochondrial dysfunction was observed in NPC1-deficient Chinese hamster ovary cells (18). Although the accumulation of cholesterol in the late endosomes and lysosomes is believed to be the cause of NPC disease, its underlying mechanism for the NPC2 deficiency-caused pathologies, especially defective autophagy in adipocytes, has not been fully understood.…”
mentioning
confidence: 99%
“…Lactate dehydrogenase catalyzes the interconversion of pyruvate and lactate. NPC1-deficient cells show increased lactate secretion, decreased glutamine-dependent mitochondrial respiration, and decreased ATP transport across mitochondrial membranes (21). Studies from NPC1-deficient mice cerebellum and cerebral cortex revealed an increase in lactate and a decrease in acetate/acetyl-CoA levels with disease progression as compared with wild-type (22).…”
Section: Corroboration Of Deps In Our Data Set With Previousmentioning
confidence: 99%
“…Energy Metabolism-Mitochondrial cholesterol accumulation can increase oxidative stress and in turn cause metabolic alterations in NPC1-deficient cells (21). Alterations in mitochondrial abundance, quality and electron transport chain have been suggested to affect energy homeostasis in the cerebellum of NPC1-deficient mice (22).…”
Section: Corroboration Of Deps In Our Data Set With Previousmentioning
confidence: 99%
“…Changes in cholesterol metabolism in the central nervous system (CNS) are linked to Alzheimer's disease, Parkinson disease, and Niemann-Pick C disease, and with mitochondrial dysfunction [188,189]. In Alzheimer's disease, -amyloid overproduction is associated with increased expression of Drp-1 and numbers of fragmented mitochondria, increased oxidative stress, and loss of ATP production, while familial Parkinson's disease has been linked to mutations in PINK1 and defective mitophagy [177].…”
Section: Pathophysiological Links Between Mitochondrial Function and mentioning
confidence: 99%